Association between home characteristics and occupant's behaviours and concentrations of bacteria, fungi and endotoxins. (January 2022) - Sousa, Joana
Abstract: Children are particularly vulnerable to airborne bacterial and fungal concentrations exposure due to the amount of time spent in indoor environments. Children bedrooms were used to investigate the prevalence of exposure to biological agents in Porto-Portugal. This study included a walkthrough inspection and biological measurements in 76 bedrooms with the purpose of identifying and analysing positive statistical associations between bacteria, fungi and endotoxins concentrations and the investigated building characteristics and occupant's behaviours. Results indicate that the use of indoor pesticides and visible presence of damp spots in the bedroom were positively associated with higher concentration of bacteria indoors. Fungi concentration was associated with several home characteristics, specifically, with the type of ceiling and floor material, visible presence of mould growth, floor cleaning and the type of rug. A positive correlation was found between the relative humidity and fungi concentration (ρ = 0.366, p  < 0.001). Endotoxins concentration was positively associated with noticeable mould odour, the heating system and the presence of cushion/pillow and rug in the bedroom. This study results demonstrate that indoor concentrations of bacteria, fungi and endotoxins are associated both to specific home characteristics and occupant's behaviour. Regarding the building characteristics building materials, dampness-related indicators and heating system were found to be the most relevant physical characteristics, as the use of indoor pesticide, fabrics presence and floor cleaning appear to be the most relevant characteristics regarding occupant's behaviour. This study results adds and contributes to the literature on exposure to indoor pollutants. Graphical abstract: Image 1 HIGHLIGHTS: Quantified biological agents were associated to children bedroom characteristics. Fungi concentrations were associated to the highest number of home characteristics. Relative humidity and fungi concentration were positively associated. Indoor pesticides use and damp spots were positively associated with bacteria. Mould odour, heating system and fabrics materials were associated with endotoxins.